Redesain Kemasan Produk Aneka Keripik Menggunakan Metode Kansei Engineering Di Desa Pesanggrahan Kesugihan - Anisha Dian Iswahyuni; Aji Kusumastuti Hendrawan (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Pesanggrahan Village, Kesugihan District, is one of the innovation villages launched by the Cilacap district government in 2022. The Kesugihan area has potential local food sources that have the potential to be developed by the community. Nuri Snack is one of the business actors engaged in food processing in the form of various chips in the form of cassava, taro and banana chips. Marketing that has been carried out at this time is selling to markets and serving purchases at home, there has been no innovation in expanding marketing to modern shops and online shops. The aims of this study were 1) to design informative packaging labels in accordance with labeling standards and 2) to develop packaging designs according to the wishes of consumers using the kansei engineering method. The method used is the kansei engineering method which translates consumer feelings into design specifications. Implementation The results of this study are in the form of label and packaging design concepts, design actors include uniqueness, product identity colors, complete product information, complete packaging information, neat, protected products, easy to carry, easy to store, have licensing and attractive designs, and the proposed packaging uses white standing pouch window doff 500z packaging with size 14cm x 23cm and chromo sticker as packaging label design. Conclusion The proposed label design already has permits and has an elegant design and is made of standing pouch plastic with a ziplock.